Stick-slip vibration analysis and vibration frequency extraction of coke pushing system. (January 2020) - Chen, Junjun; Sun, Huanwu; Jiao, Ting; Liu, Zhenguo; Xu, Bing
Highlights: A two-degree-of-freedom spring-mass-damper model is designed to study the vibration mechanism of coke pushing system. Analyze the stability and the stick-slip kinetic characteristics of the system by theoretical calculation. Obtain the vibration frequencies in different directions of the system by finite element method and verify the results by the field test. Abstract: Coke pushing equipment in the coke oven plant is a device used to push the red coke out of the coke chamber. The main section of the equipment is pushing rod and its major role is to push the ripe coke out of the furnace chamber. During the operation of pushing coke, we observe that there is an obvious vibration phenomenon. For the sake of more deeply investigating the mechanism of friction-induced vibration of the coke pushing device, we propose a mass-spring-damper model in this article. Then this model was used to research on the stability and stick-slip characteristic of the coke pushing system, and its speeds at the state of critical instability and critical stick-slip are obtained by theoretical calculation. Considering that the temperature of working environment may reach 1000 °C, numerical simulation of the coke pushing system has been carried out by finite element method, and the vibration frequencies in different directions are obtained. The simulation results show that the stick-slip vibration of 51 Hz occurs when the coke pushing device is working. Finally, the numerical simulation results are verified by the field test. The results of this paper have a certain guiding significance for improving the design of coke pushing device and reducing the vibration of the system.